Recurrent migration of peripherally inserted central catheter into the azygos vein. (23rd January 2018) - Talari, Goutham; Talari, Preetham; Parasramka, Saurabh; Mirrakhimov, Aibek E
Abstract : Peripherally inserted central catheter (PICC) migration into azygos vein (AV) is a rare complication. It is recognised only when catheter malfunction occurs or when patients develop associated complications. PICC migration into AV has been reported to be associated with various complications such as catheter malfunction, perforation, haemorrhage, thrombosis, infection and stenosis of AV. Pleural effusion and trachea–azygos fistulas have also been reported. We present a patient with recurrent migration of PICC into AV after an initial corrective repositioning during the same hospital stay. In this case, PICC migration was possibly related to left-sided approach, use of smaller diameter PICC, severe congestive heart failure and her bedbound status. PICC migration should be considered when PICC found be malfunctioning, especially if associated with the above risk factors.